1985
DOI: 10.1128/iai.50.3.647-654.1985
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in susceptibility to murine respiratory mycoplasmosis in C57BL/6 and C3H/HeN mice

Abstract: Not only is murine respiratory mycoplasmosis, due to Mycoplasma pulmonis, a complication of biomedical research, it provides excellent animal models to study the development of a naturally occurring respiratory disease induced by an infectious agent. The understanding of pathogenic mechanisms of disease can be greatly facilitated by studying genetic differences in susceptibility. Five strains of mice with various H-2K haplotypes were examined for their susceptibility to murine respiratory mycoplasmosis; of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 14 publications
5
45
0
Order By: Relevance
“…In a similar model using the mouse pathogenic mycoplasma species M. pulmonis, it was demonstrated that certain mouse strains differ markedly in resistance to infection and progression of disease with C3H/HeN mice being more susceptible than C57BL/6 mice (41). The resistance of C57BL/6 mice to M. pulmonis is thought to be related to nonspecific, innate intrapulmonary host immunity which limits the extent of infection (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar model using the mouse pathogenic mycoplasma species M. pulmonis, it was demonstrated that certain mouse strains differ markedly in resistance to infection and progression of disease with C3H/HeN mice being more susceptible than C57BL/6 mice (41). The resistance of C57BL/6 mice to M. pulmonis is thought to be related to nonspecific, innate intrapulmonary host immunity which limits the extent of infection (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar model using the mouse pathogenic mycoplasma species M. pulmonis, it was demonstrated that certain mouse strains differ markedly in resistance to infection and progression of disease with C3H/HeN mice being more susceptible than C57BL/6 mice (41). The resistance of C57BL/6 mice to M. pulmonis is thought to be related to nonspecific, innate intrapulmonary host immunity which limits the extent of infection (41,42). Cartner and coworkers have also investigated the response of various murine strains to infection with M. pulmonis by evaluating 17 inbred mouse strains, and found that resistance to murine mycoplasmosis is a complex trait controlled by multiple genes (43).…”
Section: Discussionmentioning
confidence: 99%
“…Murine respiratory mycoplasmosis is a naturally occurring disease of rats and mice; rats and mice with murine respiratory mycoplasmosis are excellent animal models for the study of infectious respiratory disease (3,4,21). It has been shown previously that C3H/HeN mice are highly susceptible to Mycoplasma pulmonis infection and disease (8). An aerosol model has been described previously (9), and pulmonary clearance of virulent M. pulmonis by C3H/HeN mice has been reported previously (25).…”
mentioning
confidence: 98%
“…Mouse strains differ in susceptibility to M. pulmonis, and studies of these differences give insights into the mechanisms of host defense and pathogenesis of respiratory mycoplasmosis. During the first 2 weeks of infection (acute disease), C3H/ HeN mice are much more susceptible to the infection than C57BL/6N mice, as evidenced by the fact that C3H/HeN mice have a 100-fold-lower 50% gross pneumonia dose, 50% microscopic lesion dose, and 50% lethal dose (10,24). However, it is not known whether the differences in susceptibility persist during the chronic disease (2 weeks to 2 months) or how antibody responses of the two mouse strains relate to progression of the chronic disease.…”
mentioning
confidence: 99%